Highly functional mortar composition and mortar cured body
A mortar composition using Portland cement, blast furnace slag powder, and reinforced fibers enables high compression strength at room temperature, addressing the need for high-temperature curing and strength reduction issues in blast furnace cement mortars, enhancing on-site manageability and durability.
Patent Information
- Application Number
- JP2023119328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Mortar using blast furnace cement requires high-temperature curing to achieve sufficient compression strength and is prone to reduced strength compared to Portland cement, necessitating careful initial curing to fully demonstrate its characteristics.
A mortar composition comprising Portland cement, blast furnace slag powder, a strength promotion agent, a water-reducing agent, and fine aggregate, with specific ratios and the addition of reinforced short fibers, allowing room temperature curing to achieve high compression strength.
The mortar composition achieves high compression strength and improved toughness through room temperature curing, facilitating easier on-site management and reducing the risk of cracking due to shrinkage.
Smart Images

Figure 2025016201000005 
Figure 2025016201000001 
Figure 2025016201000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a highly functional mortar composition, a mortar, and a hardened mortar using blast-furnace cement obtained by mixing ground granulated blast-furnace slag and Portland cement. [Background technology]
[0002] Mortar made by adding water to blast-furnace cement, which is a mixture of ground granulated blast-furnace slag and Portland cement, has high long-term strength and is excellent at suppressing alkali-silica reaction and salt penetration, as described in Non-Patent Document 1 below, and is used in civil engineering structures, etc. However, since mortar using blast-furnace cement is slow to develop strength, care must be taken, such as time and effort in initial curing, in order to fully utilize its properties. In addition, as described in Patent Document 1 below, mortar using blast-furnace cement tends to have a lower compressive strength of the resulting cast mortar body compared to mortar using only Portland cement. In order to improve the compressive strength of the cast mortar body, curing at a temperature higher than room temperature, such as steam curing, is required. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-125371 A [Non-patent literature]
[0004] [Non-Patent Document 1] Nippon Steel & Sumitomo Metal Techniques No. 399 (2014) pp. 115-120 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention aims to provide a highly functional mortar composition containing blast furnace cement, a mortar, and a hardened mortar body that can develop sufficient compressive strength by simply curing at room temperature a mortar body cast into a specified shape. [Means for solving the problem]
[0006] The present invention, which has been made to achieve the above object, is a mortar composition containing Portland cement, ground granulated blast furnace slag, a strength enhancer, a water reducing agent, and fine aggregate, the specific surface area of which is 2250 cm per 100 parts by mass of the Portland cement. 2 The highly functional mortar composition is characterized by comprising a maximum of 70 parts by mass of the ground granulated blast furnace slag having a viscosity of 100 / g or more, 3 to 20 parts by mass of the strength enhancer containing calcium aluminate, 0.2 to 1.0 part by mass of the water reducer containing polycarboxylic acid ether, and 5 to 30 parts by mass of the fine aggregate.
[0007] The Portland cement, the ground granulated blast furnace slag, the strength enhancer, the water reducing agent, and the fine aggregate are preferably in powder form, which facilitates storage of the mortar composition.
[0008] The present invention also provides a mortar, characterized in that water is added to the mortar composition described above so that the water-to-binder ratio relative to the binder consisting of the Portland cement, the ground granulated blast furnace slag, and the strength enhancer is 28 to 33%.
[0009] By adding reinforcing short fibers at a fiber volume ratio of 0.5 to 1% per 100 parts by volume of the mortar, the reinforcing short fibers are dispersed in the hardened mortar body, thereby improving the bending toughness of the hardened mortar body.
[0010] Furthermore, the present invention relates to a mortar body in which the above-mentioned mortar is cast and solidified into a predetermined shape, and the mortar body has a compressive strength of 88 N / mm2 when cured in air at 20°C ± 3°C for 28 days. 2 The hardened mortar body is characterized by having been hardened as described above.
[0011] The present invention relates to a mortar cast body in which the above-mentioned mortar is cast and solidified into a predetermined shape, and the mortar cast body is cured in air at 20°C ± 3°C for one day, then cured in water at 20°C ± 3°C for 3 to 7 days, and then further cured in air at 20°C ± 3°C for 28 days, and the compressive strength of the mortar cast body is 150 N / mm 2 The hardened mortar body is characterized by having been hardened as described above. Effect of the Invention
[0012] According to the present invention, a hardened mortar having high compressive strength can be obtained by only subjecting a cast mortar body obtained from a mortar composition containing blast-furnace cement to air curing, thereby simplifying on-site curing management. [Brief description of the drawings]
[0013] [Figure 1] 1 is a graph showing the difference in bending moment between the presence and absence of mixed short steel fibers in the hardened mortar body according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The Portland cement used in the present invention may be ordinary Portland cement. Depending on the object of construction, any of high-early-strength Portland cement, ultra-high-early-strength Portland cement, moderate-heat Portland cement, low-heat Portland cement, and sulfate-resistant Portland cement may be selected and used.
[0015] The blast furnace slag powder used in combination with Portland cement has a specific surface area of 2250 cm 2 / g or more. Ground granulated blast furnace slag is divided into four classes based on specific surface area. Class 3000 (2250 cm 2 / g or more, 3500cm 2 / g), Class 4000 (3500cm 2 / g or more, 5000cm 2 / g), Class 6000 (5000cm2 / g or more, 7000cm 2 / g), Class 8000 (7000cm 2 / g or more, 10000cm 2 / g). The larger the specific surface area of such ground granulated blast furnace slag is, the higher the reactivity is, and the ground granulated blast furnace slag can be selected according to the required properties such as the strength and durability of the obtained hardened mortar. In the present invention, the ground granulated blast furnace slag is preferably class 6000, and ESMENT SUPER 60P (product name) manufactured by NIPPON STEEL Blast Furnace Cement Co., Ltd. can be suitably used. The amount of the ground granulated blast furnace slag is at most 70 parts by mass per 100 parts by mass of Portland cement. The lower limit is preferably 5 parts by mass. It is preferably 10 to 70 parts by mass, more preferably 10 to 40 parts by mass, and even more preferably 20 to 30 parts by mass. If the amount of the ground granulated blast furnace slag exceeds 70 parts by mass, the kneadability of the mortar is significantly reduced.
[0016] Strength enhancers used in combination with Portland cement and ground granulated blast furnace slag may contain calcium aluminate. Denka ES-L manufactured by Denka Co., Ltd. may be suitably used as such a strength enhancer. The blending amount of such a strength enhancer is 3 to 10 parts by mass, preferably 5 to 6 parts by mass, per 100 parts by mass of Portland cement. If the blending amount of the strength enhancer is less than 3 parts by mass, the initial compressive strength of the cast mortar body decreases, and if the blending amount exceeds 10 parts by mass, the hardening speed of the mortar increases significantly, and the handling property of the mortar decreases.
[0017] In addition, a polycarboxylic acid ether-containing water-reducing agent is used. When water is added to a mortar composition using other water-reducing agents and kneaded, bleeding, in which water bleeds out, tends to occur. Examples of water-reducing agents containing polycarboxylic acid ether include Leopak G-200 and G-200 (both trade names) manufactured by Lion Specialty Chemicals Co., Ltd. and MELFLUX6681F and MELFLUX5581F (both trade names) manufactured by SKW East Asia Co., Ltd. In particular, Leopak G-200 manufactured by Lion Specialty Chemicals Co., Ltd. can be preferably used. The amount of such a water-reducing agent to be used is 0.2 to 1.0 parts by mass, preferably 0.2 to 0.5 parts by mass, and more preferably 0.2 to 0.3 parts by mass, relative to 100 parts by mass of Portland cement. If the amount of this water-reducing agent to be used is less than 0.2 parts by mass, the kneadability is significantly reduced, and if it exceeds 1.0 part by mass, bleeding tends to occur. When a melamine sulfonic acid-based water reducing agent is used in place of the polycarboxylic acid ether-containing water reducing agent, bleeding is more likely to occur.
[0018] Furthermore, as the fine aggregate, silica sand with 85% or more of particles with a particle size of 0.3 mm or less can be preferably used, and No. 7 silica sand with a particle size of 0.2 mm or less can be preferably used. The amount of fine aggregate used is 5 to 30 parts by mass per 100 parts by mass of Portland cement. If the amount of fine aggregate is less than 5 parts by mass, the mortar kneaded with water becomes highly viscous and difficult to handle, and if the amount exceeds 30 parts by mass, bleeding is likely to occur.
[0019] It is preferable that the materials constituting the mortar composition are in powder form, since this makes it easier to store and transport the materials in a mixed state. In addition, since the specified materials are in powder form, they can be easily made into a paste-like mortar by simply adding water and kneading them on-site.
[0020] The amount of water added to the powdered mortar composition is such that the water-binder ratio relative to the binder (hydraulic material) consisting of Portland cement, ground granulated blast furnace slag, and strength enhancer is 28-33%, preferably 28-31%, and more preferably 29-30%. If the water-binder ratio is less than 28%, the kneadability decreases, and if the water-binder ratio exceeds 33%, the compressive strength of the obtained hardened mortar decreases.
[0021] By adding reinforcing short fibers at a fiber volume ratio of 0.5 to 2%, preferably 0.8 to 1.2%, to 100 parts by volume of the paste-like mortar kneaded with a predetermined amount of water, the bending toughness of the finally obtained hardened mortar can be significantly improved, which is preferable. The reinforcing short fibers may be metal fibers such as steel, polymer fibers, or natural fibers, and the fiber length is 5 to 15 mm, preferably 9 to 15 mm, and more preferably 10 to 13 mm, so that the reinforcing short fibers can be uniformly kneaded into the paste-like mortar. The reinforcing short fibers may be added to the powdered mortar composition.
[0022] A paste-like mortar is prepared by adding a predetermined amount of water to the powdered mortar composition and kneading it, and then poured into a predetermined shape and immediately cured to harden. The poured mortar of the present invention is cured in air at 20°C±3°C for 28 days to become a hardened mortar. The compressive strength of the obtained hardened mortar is 88N / mm 2 That is all. The reason why the cast mortar of the present invention hardens by a short period of air curing is presumably because the calcium aluminate contained in the strength enhancer in the mortar composition hardens and exhibits strength in a short period of time, and strength is developed in combination with the formation of ettringite (3CaO·AL2O3·3CaOSO4·32H2O) by components such as CaO and Al2O3 contained in the ground granulated blast furnace slag. However, although ettringite generated in the cast mortar allows the cast mortar to develop its strength early, if the amount of ettringite generated is excessive, it may expand the resulting hardened mortar and cause cracks.
[0023] To increase the compressive strength of the mortar hardened body compared to that which has been subjected to such air curing, it is preferable to combine short-term underwater curing and air curing. That is, the mortar cast body, in which paste-like mortar is poured and hardened into a predetermined shape, is cured in air at 20°C±3°C for one day, then cured in water at 20°C±3°C for 3 to 7 days, and then cured in air at 20°C±3°C for a further 21 days. The compressive strength of the hardened mortar body thus hardened is 150N / mm 2 The reason why the hardening of the cast mortar according to the present invention progresses by combining short-term underwater curing and air curing is presumed to be as follows. In other words, water is essential for the hardening reaction of mortar. If the mortar body is exposed to air immediately after casting and dried, there will be a shortage of water necessary for the hardening reaction, and it will not develop sufficient strength. Therefore, the mortar body is cured underwater after casting to prevent drying, and then cured in air to achieve sufficient strength development. By curing the mortar body underwater for several days after casting, the hardening reaction progresses to a certain extent and the structure becomes dense, and even if it is removed from the water, drying is suppressed, so the hardening reaction continues to progress over the long term and strength is increased.
[0024] Furthermore, when the paste-like mortar body hardens, the body may shrink due to a hydration reaction between the water binder components and water, but the mortar of the present invention does not shrink but shows slight expansion when it hardens from the paste-like body, thereby preventing cracks in the hardened mortar body due to shrinkage. EXAMPLES
[0025] Examples of the present invention will be described in detail below, but the scope of the present invention is not limited to these examples.
[0026] Example 1 (raw materials) The raw materials used for the mortar composition are shown in Table 1 below. These are in powder form, and the mortar composition was prepared by mixing the raw materials in the ratio shown in Table 2.
[0027] [Table 1]
[0028] [Table 2]
[0029] The raw materials were mixed in the proportions shown in Table 2, and water was added to the total amount of each mortar composition to obtain a paste-like mortar, so that the ratio of the amount of water to the total amount of each mortar composition (water-mortar ratio) was 27%. The water-binder ratio at this time is shown in Table 3. The initial setting time of this paste-like mortar was measured in accordance with the setting test of JIS R5201 "Physical Test Methods for Cement" and is also shown in Table 3. The initial setting time indicates the initial time at which the mortar loses fluidity due to hydration reaction and gradually hardens. If this initial setting time is too long, when the mortar is used as an anchor adhesive, the anchor bar may tilt when it is struck horizontally after casting, so it is preferable that the initial setting time is 70 minutes or less. In addition, the paste-like mortar was cast into a cylindrical shape of 50 mm x 100 mm, and the mortar cast was left to stand for one day to harden, and then cured in air at 20 ° C ± 3 ° C for 28 days to obtain a hardened mortar. The compressive strength was measured in accordance with JIS-R 5210:2015, and the results are shown in Table 3 as "28D compressive strength."
[0030] [Table 3] As is clear from Table 3, the initial setting time was short at 27 minutes or less, and the compressive strength of the hardened mortar was 88 N / mm 2The results were as above. Thus, the hardened mortar of this embodiment can obtain high compressive strength only by air curing at room temperature. In addition, in order to measure the volume change when hardening from a paste-like mortar, the volume change of the hardened mortar of the poured mortar of Mixture 1, which was hardened by air curing at 20°C ± 3°C for 7 days, was measured in accordance with JSCE-F532-2013, and it was found to have expanded slightly by 0.17%. The water-binder ratio in Table 3 is the ratio of the amount of water to the water-binding component.
[0031] Example 2 Water was added to the mortar composition of Mixture 1 in Table 2 so that the water-mortar ratio was 27%, and the resulting paste-like mortar was kneaded and cast in the same manner as in Example 1 to obtain a cast mortar body of a predetermined shape. This cast mortar body was cured in air at 20°C±3°C for 1 day, then cured in water at 20°C±3°C for 3 to 7 days, and further cured in air at 20°C±3°C for 28 days to obtain a hardened mortar body. The compressive strength of this hardened mortar body was measured in the same manner as in Example 1, and was found to be 153 N / mm 2 In this way, the hardened mortar of this example achieved a compressive strength of 150 N / mm 2 It is possible to obtain a compressive strength exceeding the limit.
[0032] Example 3 Water was added to the mortar composition of Mixture 1 in Table 2 so that the water-mortar ratio was 27%, and kneaded to obtain a paste-like mortar of 100 parts by volume. Steel short fibers with a fiber length of 13 mm were added to the paste-like mortar so that the fiber ratio was 1%, and kneaded to obtain a fiber-containing mortar. When this fiber-containing mortar was cast into a specified shape and the cross section of the cast mortar was observed, the dispersion of the steel short fibers was good, and no unevenness or lumps of the steel short fibers were observed.
[0033] The fluidity of the fiber-reinforced mortar was measured in accordance with JIS-R 5201:2015. The zero-stroke flow value, measured without subjecting the paste-like fiber-reinforced mortar to vibration or impact, was 275 mm. Similarly, water was added to the mortar composition of Mixture 1 in Table 2 so that the water-mortar ratio was 27%, and the paste-like mortar before the addition of the short steel fibers had a zero-stroke flow value of 277 mm. Thus, the fluidity of the fiber-reinforced mortar was good.
[0034] The fiber-containing mortar was left to harden for one day in the same manner as in Mixture 1 in Table 2, and then the bending toughness was measured during air curing at 20°C ± 3°C. The bending toughness was measured in accordance with JIS-R 5201:2015. The results are shown in Figure 1. Similarly, the bending toughness during air curing was measured for the mortar of Mixture 1 in Table 2, and the results are also shown in Figure 1. As is clear from Figure 1, the bending toughness of the mortar containing fiber is improved compared to the mortar containing no fiber.
[0035] Example 4, Comparative Example 1 The adjustment ratio shown in Table 2 was changed as shown in Table 4, and water was added so that the water-mortar ratio was 27% (water-combined ratio 29%). The initial setting time of the paste-like mortar was measured in the same manner as in Example 1, and the results are shown in Table 4. The paste-like mortar was cast in the same manner as in Example 1 to obtain a cast mortar body of a predetermined shape. The cast mortar body was cast into a cylindrical shape of 50 mm x 100 mm, and left to stand for one day to harden, and then cured in air at 20 ° C. ± 3 ° C. for 28 days to obtain a hardened mortar body. The compressive strength was measured in accordance with JIS-R 5210:2015. The results are shown in Table 4.
[0036] [Table 4]
[0037] As is clear from Table 4, the mixtures 8 to 13 within the scope of the present invention have initial setting times of 70 minutes or less and a compressive strength of the hardened mortar of 88 N / mm 2 However, in the case of Mixture 14 of Comparative Example 1, in which the strength enhancer is outside the scope of the present invention, the initial setting time was abnormally long at 130 minutes or more, which was not practical, and the compressive strength was only 88 N / mm 2 is less than. Here, when the amount of ground granulated blast furnace slag exceeded 70 parts by mass per 100 parts by mass of ordinary Portland cement, the mixing properties of the mortar significantly decreased, making it difficult to mix sufficiently and impossible to cast into a cylindrical shape, so measurements of the compressive strength of the hardened mortar were discontinued. Also, when the amount of strength enhancer exceeded 10 parts by mass, the hardening speed of the mortar became significantly faster, making the mortar significantly less easy to handle and impossible to cast into a cylindrical shape, so measurements of the compressive strength of the hardened mortar were discontinued.
[0038] Comparative Example 2 In Mixture 1 in Table 2, MetaMax (product name: manufactured by SKW East Asia Co., Ltd.), a metakaolin-based strength enhancer, was used as the strength enhancer. The composition was the same as in Table 2, but the same procedure was followed as in Table 3 to measure the compressive strength of the hardened mortar. The result was 66.8 N / mm 2 and 88N / mm 2 The results were as follows.
[0039] Comparative Example 3 In Mixture 1 of Table 2, the melamine sulfonic acid-based water-reducing agent MELMENT F10M (product name, manufactured by BASF) was used as the water-reducing agent. The composition was the same as in Table 2, except that a mortar was cast in the same manner as in Table 3. However, bleeding occurred, so further operations were discontinued. [Industrial Applicability]
[0040] The functional mortar composition according to the present invention can be used for anchors and grouts.
Claims
1. A mortar composition comprising Portland cement, ground granulated blast furnace slag, a strength enhancer, a water reducer, and fine aggregate, The specific surface area is 2250 cm for 100 parts by mass of the Portland cement. 2 The highly functional mortar composition is characterized by comprising a maximum of 70 parts by mass of the ground granulated blast furnace slag having a particle size of 0.1 to 1.0 mm / g or more, 3 to 10 parts by mass of the strength enhancer containing calcium aluminate, 0.2 to 1.0 part by mass of the water reducer containing polycarboxylate ether, and 5 to 30 parts by mass of the fine aggregate having a particle size of 0.2 mm or less.
2. 2. The highly functional mortar composition according to claim 1, wherein the Portland cement, the ground granulated blast furnace slag, the strength enhancer, the water reducing agent, and the fine aggregate are in powder form.
3. A mortar comprising the high-performance mortar composition according to claim 1, and water added thereto such that the water-to-binder ratio relative to the binder consisting of the Portland cement, the ground granulated blast furnace slag, and the strength enhancer is 28 to 33%.
4. 4. The mortar according to claim 3, wherein reinforcing short fibers are added at a fiber volume ratio of 0.5 to 1% per 100 parts by volume of the mortar.
5. The mortar body according to claim 3 is formed by pouring and solidifying the mortar into a predetermined shape, The mortar body has a compressive strength of 88 N / mm when it is cured in air for 28 days at 20°C ± 3°C. 2 A hardened mortar body characterized by having been hardened as described above.
6. The mortar body according to claim 3 is formed by pouring and solidifying the mortar into a predetermined shape, The mortar body is cured in air at 20°C ± 3°C for 1 day, then cured in water at 20°C ± 3°C for 3 to 7 days, and then cured in air at 20°C ± 3°C for 28 days. The compressive strength of the mortar body is 150 N / mm 2 A hardened mortar body characterized by having been hardened as described above.
Citation Information
Patent Citations
Hydraulic blast furnace slag composition and concrete cured body
JP2014125371A